Neutral Turkmenistan: Approaches to Regional Security - Y. A. Kepbanov (Московский журнал международного права)
After the collapse of the USSR there were formed several countries and each country had to make a choice with regard to its model of external relations and security. Turkmenistan chose the status of total neutrality and it had been a natural reaction to the geopolitical situation in which the country appeared to be.Policy of neutrality is a way of preserving security of a nation and a state, thus providing for the international peace and stability in the region.In 1995 the neutral status of Turkmenistan had been recognized by an international community through the Resolution of the UN General Assembly 50/80. This Resolution has wide implications both for Turkmenistan and the international community. Turkmenistan on the one hand received international guarantees of its security and territorial integrity; on the other hand it refused from its several rights, accepted some obligations as a state and it cannot reject this status unilaterally.But the neutrality status does not prohibit international contacts and the membership in international organizations. Turkmenistan is a member of more than 40 international organizations. Also Turkmenistan is a signatory nearly to all of the international treaties banning the use, proliferation of weapons of mass destruction. Apart from this Turkmenistan played an important role in conflicts in Tajikistan and Afghanistan.One of the key directions of the external policy of neutrality is international economic cooperation. By taking an active part in international economic cooperation Turkmenistan facilitates the strengthening of regional and international security what is the primary goal of the Turkmenistan’s neutrality.